Endogenous rRNA Sequence Variation Can Regulate Stress Response Gene Expression and Phenotype - Kurylo, Chad M. (Cell Rep, 2018)
Prevailing dogma holds that ribosomes are uniform in composition and function. Here, we show that nutrient limitation-induced stress in E. coli changes the relative expression of rDNA operons to alter the rRNA composition within the actively translating ribosome pool. The most upregulated operon encodes the unique 16S rRNA, rrsH, distinguished by conserved sequence variation within the small ribosomal subunit. rrsH-bearing ribosomes affect the expression of functionally coherent gene sets and alter the levels of the RpoS sigma factor, the master regulator of the general stress response. These impacts are associated with phenotypic changes in antibiotic sensitivity, biofilm formation, and cell motility and are regulated by stress response proteins, RelA and RelE, as well as the metabolic enzyme and virulence-associated protein, AdhE. These findings establish that endogenously encoded, naturally occurring rRNA sequence variation can modulate ribosome function, central aspects of gene expression regulation, and cellular physiology.